The Influence of Customer Experience in Thai Full-Service Restaurant towards Customer Satisfaction with Consumption Emotion as Mediator: International Tourists’ Perspective - Chewwasung, Kritta-orn (วารสารสันติศึกษาปริทรรศน์ มจร, 2022)
This research aimed to study (1) the influence of customer experience in Thai full-service restaurants toward customer satisfaction (2) to investigate the mediating effect of customer emotion between customer experience and customer satisfaction. The sample size was 400 international tourists who visited Thai full-service restaurants, the respondents were selected by purposive sampling. The sample group was selected from international tourist who visited Thai full-service restaurant according to the provided list. Analysis the data by the descriptive statistic and the Structural Equation Model use to analyze the causal relationship between customer and experience and have consumption emotion as the mediating factor. The research result was found as follows. 1. The result indicated that customer experience insignificantly influenced on customer satisfaction. 2. The customer experience indirectly influenced customer satisfaction by passing through the consumption emotion as the mediating factor. 3. Thai full-service restaurant operators should pay attention to the design of experience touchpoints that influence the consumption emotion to construct customer satisfaction, leading to competitive advantage and creating sustainable operation in the highly competitive restaurant business.